Armenian Adaptations of the Fairy Tale “Cinderella” in the Panorama of World Fairy Tales - Soghoyan, Astghik (Bulletin of Yerevan University B: Philology, 2022)
The article is devoted to the study of Armenian literary versions of the fairy tale about Cinderella. Fairy tales corresponding to two variants of the classification model of Aarne-Thompson-Uther tales - ATU510A and ATU510B are considered: the works of Tlkatintsi "A thorn in my garden" and "Mariam" by Raphael Patkanyan. Structural and psychoanalytic studies have been carried out, the expressions of the Elektra complex underlying the fairy tale, and the manifestations of the ritual of the change of seasons have been identified. The article also explores the unique Western Armenian translation of the fairy tale "Mokhranush", which is considered for the first time.